Analytical QbD-Integrated Method Development and Validation of Silver Sulphadiazine in Pure Drug and Topical Nanocarrier(s). Issue 6 (2nd November 2018) - Thakur, Kanika; Sharma, Gajanand; Singh, Bhupinder; Chhibber, Sanjay; Katare, Om Prakash
Abstract: Current work aims at Analytical Quality by Design (AQbD)-based development and validation of stability-indicating chromatographic method for quantification of silver sulphadiazine (SSD) in bulk and pharmaceutical dosage forms. The first stage of AQbD approach involved defining QTP (Quality Target Profile) usually referred to as ATP (Analytical Target Profile). Screening studies were performed employing a 78-Taguchi design. The composition of mobile phase, pH of water and injection volume were identified as critical method parameters (CMPs) and were systematically optimized using I -optimal design for evaluating CAAs, namely theoretical plates, tailing factor and % assay. Chromatographic separation was carried out using C-18 column with water containing glacial acetic acid (5 mL in 255 mL water, pH adjusted to 2.5) and mixture of acetonitrile:methanol (75: 25, v/v) in the ratio of 80: 20 (v/v) as mobile phase at flow rate of 0.7 mL/min at 254 nm. The method was validated as per ICH recommended guidelines. Further, forced degradation studies and application of the developed method for the estimation of SSD in marketed, liposomal and organogel systems indicated no significant change in retention time. In conclusion, the studies successfully ratify the utility of AQbD approach for developing highly sensitive liquid chromatographic method for SSD estimation.